Radiation dose study of LINAC source around healthy organs in cancer examination using farmer chamber ionization detector - Fardela, Ramacos; Candra, Ega Septryan; Milvita, Dian; Mardiansyah, Dedi; Ridwan; Diyona, Fiqi (Penerbit Universiti Kebangsaan Malaysia, 2025)
Cancer treatment using ionizing radiation is known to cause damage to healthy tissue around the target. Therefore, this study aimed to measure the dose in the area around the cancer target to ensure the amount received by the patient does not exceed the specified tolerance limit. Measurements were performed using a Farmer-type ionization chamber detector on a phantom slab. The variations in the field area used were 5 × 5 cm2 and 10 × 10 cm2 at depths of 1.5 cm, 4 cm, 6 cm, 8 cm, and 10 cm, as well as a distance of 3 cm, 5 cm, 7 cm, 10 cm, and 15 cm outside the radiation field. The dose value was measured based on the IAEA TRS No.398 protocol. The results showed that the percentage of the dose decreased below 10% at a distance of 5 cm for a field area of 5 × 5 cm2. Meanwhile, for a field area of 10 × 10 cm2, the percentage of the dose decreased below 10% after passing a distance of 7 cm from the edge of the radiation field. Based on the results, the percentage of the measured dose was greater for the enlarged depth. Areas outside the cancer target still receive unneeded radiation doses. The value of the dose received depends on the energy used, the size of the field, and the distance from the edge of the field.